2001
DOI: 10.1002/da.1053
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of nonresponse to pharmacotherapy in panic disorder: A review

Abstract: Several effective pharmacotherapeutic treatments exist for panic disorder; however, not all patients respond to treatment: between 20% to 40% are non-responders. Recent studies have reported several predictors of nonresponse to pharmacotherapy. In this review two questions are addressed: is there consensus with respect to predictors of nonresponse and are there any differences between short-term and long-term predictors? In this review both short-term and long-term outcome studies are discussed. Studies were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 92 publications
(143 reference statements)
2
55
2
1
Order By: Relevance
“…Some of the documented predictors of treatment effect found in mixed-age populations, such as duration of symptoms for both CBT and pharmacological treatment outcome (Scheibe and Albus, 1997;Slaap and den Boer, 2001;Stein et al, 2001;Solvason et al, 2003) and depressive symptoms for pharmacological treatment outcome (Stein et al, 2001) were not found to be related to outcome in our study. It should be noted, however, that some of the analyses reported in this study may have failed to reach statistical significance due to small sample size, as discussed below.…”
Section: Variables Predicting Treatment Responsecontrasting
confidence: 73%
“…Some of the documented predictors of treatment effect found in mixed-age populations, such as duration of symptoms for both CBT and pharmacological treatment outcome (Scheibe and Albus, 1997;Slaap and den Boer, 2001;Stein et al, 2001;Solvason et al, 2003) and depressive symptoms for pharmacological treatment outcome (Stein et al, 2001) were not found to be related to outcome in our study. It should be noted, however, that some of the analyses reported in this study may have failed to reach statistical significance due to small sample size, as discussed below.…”
Section: Variables Predicting Treatment Responsecontrasting
confidence: 73%
“…Moreover, having a PD represents a strong vulnerability factor for developing other axis I disorders (Stein et al, 1993). Second, treatment of comorbid PDs are normally more complex and less optimistic than treatment of axis I comorbidities due to less favourable outcomes (Reich, 2003;Slaap and den Boer, 2001;Telch et al, 2011), higher drop-out rates (Sanderson et al, 2002), less positive patient expectations (Martino et al, 2012) and more challenges with establishing a durable and flexible therapeutic alliance (Bienenfeld, 2007;Martino et al, 2012).…”
mentioning
confidence: 99%
“…Sin embargo, es importante señalar que se produce una gran variabilidad en las estimaciones de la prevalencia. Esta variabilidad es probablemente debida a las diferencias en los instrumentos de evaluación y diagnóstico utilizados y a la población estudiada (Slaap y den Boer, 2001).…”
Section: Resultsunclassified